COVID-19 vaccine hesitancy among the Chinese elderly: A multi-stakeholder qualitative study - Xiaoyu Li; Yanping Bai; Lijun Weng; Yunshan Bai; Wenjie Gong (Taylor & Francis Group, 2024)
ABSTRACTThe United Nations reported that the mortality risk of Corona Virus Disease 2019 (COVID-19) is five times higher in the elderly than the global average. Although the COVID-19 vaccine effectively prevents infections and reduce mortality among the elderly, vaccine hesitancy among the Chinese elderly poses a significant threat. This study, utilizing the "Confidence, Convenience and Complacency (3 Cs)" vaccine hesitancy model, aimed to explore factors contributing to vaccine hesitancy among the Chinese elderly and assess national countermeasures and potential improvement approaches. Thirteen elderly with vaccine hesitancy and eleven vaccine-related staff participated in semi-structured interviews. Thematic analysis revealed three key determinants of vaccine hesitancy among the elderly: perceived low threat of COVID-19, lack of confidence in COVID-19 vaccine, and poor accessibility to vaccination. China has implemented strategies, including advocacy through diverse channels, joint multi-sectoral promotion vaccination, and enhancing ongoing vaccination services. Recommendations from the vaccine-related staff emphasize improving vaccine awareness among the elderly, and prioritizing the vaccination environment and process. The study underscores the importance of targeted vaccination promotion programs addressing hesitation reasons to improve vaccination rates. Furthermore, existing countermeasures can serve as a foundation for enhancing vaccination strategies, including improved publicity, administration, and management approaches.